Methyl cellosolve-induced hepatic oxidative stress: The modulatory effect of syringic acid on Nrf2-Keap1-Hmox1-NQO1 signaling pathway in rats - Oluwatobi T. Somade; Babatunji E. Oyinloye; Basiru O. Ajiboye; Olukemi A. Osukoya (Elsevier, 2023)
Ethnopharmacological relevance: Syringic acid (SAC) is a phenolic compound and an antioxidant that has been identified in honey, grapes, red wine, marigold and sugar apple. Due to its potent antioxidant prowess, SAC possesses hepatoprotective, nephroprotective, neuroprotective, cardioprotective and anti-inflammatory activities. Aim of the study: Judging by these credentials, this study investigated the effect of 25, 50 and 75 mg/kg body weight of SAC on hepatotoxicity induced by 100 mg/kg body weight of methyl cellosolve (MECE) in male Wistar rats. Results: Compared with control, MECE decreased the liver relative weight, nitric oxide (NO) concentration, glutathione S-transferase (GST), glutathione peroxidase (GPx), catalase (CAT) and superoxide dismutase (SOD) activities, while liver malondialdehyde (MDA), nuclear factor erythroid 2-related factor 2 (Nrf2), Kelch-like ECH associated protein 1 (Keap1), heme oxygenase 1 (Hmox1) and NAD(P)H quinone oxidoreductase 1 (NQO1) levels were significantly increased. Treatments with 25, 50 and 75 mg/kg of SAC significantly decreased the concentration of MDA, Nrf2, Keap1 (by 50 and 75 mg/kg only), mRNA expressions of Hmox1, NQO1 and increased the concentration of NO, activities of GPx, GST, SOD and CAT compared with MECE only administered rats. Conclusion: In conclusion, SAC demonstrated a strong hepatoprotective role against MECE-induced hepatic depletion of endogenous antioxidant enzymes and inhibition of MECE-induced cytosolic Nrf2 activation and antioxidant response element (ARE)-dependent genes in rats.